Factors Associated with the Use of Traditional Health Services in Indonesia: A Secondary Analysis of the Indonesian Basic Health Research - Rifka, Niswatul; Idris, Haerawati (UI Scholars Hub, 2023)
Background: Traditional health services in Indonesia have been used increasingly over the past few years because patients nowadays are more proactive in seeking various alternative modes of self-care. This study aimed to analyze factors associated with the use of traditional health services in Indonesia. Methods: This quantitative study used a cross-sectional research design. The research data were secondary data from the 2018 Indonesian Basic Health Research. The research samples were 163,259 respondents aged >10 years and the statistical test for data analysis was multiple logistic regression. Results: The percentage of respondents who used traditional health services was 73.8%. The bivariate results in this study indicate that age, gender, employment status, educational level, residence, marital status, and access to health facilities had a significant relationship with the use of traditional health services. Conclusions: The use of traditional health services was influenced by age, gender, residence, marital status, and distance. The Indonesian government needs to consider these factors when extending the use of traditional health services.